3D NMR structure of a complex between the amyloid beta peptide (1–40) and the polyphenol ε-viniferin glucoside: Implications in Alzheimer's disease - Richard, Tristan; Papastamoulis, Yorgos; Waffo-Teguo, Pierre; Monti, Jean-Pierre (Biochimica et biophysica acta, 2013)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder. There is a consensus that Aβ is a pathologic agent and that its toxic effects, which are at present incompletely understood, may occur through several potential mechanisms. Polyphenols are known to have wide-ranging properties with regard to health and for helping to prevent various diseases like neurodegenerative disorders. Thus inhibiting the formation of toxic Aβ assemblies is a reasonable hypothesis to prevent and perhaps treat AD Solution NMR and molecular modeling were used to obtain more information about the interaction between the Aβ1–40 and the polyphenol ε-viniferin glucoside (EVG) and particularly the Aβ residues involved in the complex. The study demonstrates the formation of a complex between two EVG molecules and Aβ1–40 in peptide characteristic regions that could be in agreement with the inhibition of aggregation. Indeed, in previous studies, we reported that EVG strongly inhibited in vitro the fibril formation of the full length peptides Aβ1–40 and Aβ1–42, and had a strong protective effect against PC12 cell death induced by these peptides. For the full length peptide Aβ1–40, the binding sites observed could explain the EVG inhibitory effect on fibrillization and thus prevent amyloidogenic neurotoxicity. Even though this interaction might be important at the biological level to explain the protective effect of polyphenols in neurodegenerative diseases, caution is required when extrapolating this in vitro model to human physiology. •A molecular interaction between the Aβ1–40 and the polyphenol EVG is showed.•The NMR 3D structure of the complex is proposed.•This interaction might explain the protective effect of polyphenols in neurodegenerative diseases.